Perancangan UI/UX Aplikasi Mobile untuk Pencegah Stunting pada Anak di Indonesia Menggunakan Metode Design Thinking - Hen Hen Lukmana; Muhamad Al-Husaini (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Stunting, a chronic nutritional problem in Indonesia with a prevalence rate of 24.4% among under-fives, is caused by chronic malnutrition and recurrent infections that hinder child growth. Lack of awareness about nutrition and prevention exacerbates the issue. Digital solutions can play a key role in addressing this problem by enabling online health and nutrition monitoring. This research focuses on designing a UI/UX mobile application to aid parents in monitoring and educating about stunting. The Design Thinking approach, involving stages such as Empathize, Define, Ideate, Prototype, and Test, was used to develop the application. The resulting UI/UX design achieved good user experience, with an average System Usability Scale (SUS) score of 75.375, categorizing it as grade B. The application includes educational, early detection, and consultation features to support parents, health workers, and policymakers in combating stunting in Indonesia.